Kepemilikan Manajerial, Kepemilikan Institusional, Kepemilikan Asing dan Manajemen Laba - Fulgentius Lambertus Januartha; Hasim As’ari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial statements in a company are very crucial because they provide information about the state and performance of the company. The high level of competition between companies encourages management to manage profits. The practice of altering a company's financial accounts to appear stable to extract profits for oneself or the company and attract stakeholders to invest cash in them is known as profit management. However, profit management is not considered fraudulent if it follows the applicable accounting methods and standards. However, the information generated remains different from reality and can influence decision-making. In this context, agency theory explains that a contract between an agent and a principal involves two parties who each seek to benefit themselves, which can lead to conflict. This study aims to determine how managerial ownership, institutional ownership, and foreign ownership affect the profit management of manufacturing companies in the consumer services sub-sector listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Eleven companies formed the sample, while 47 companies in the consumer services sub-sector made up the study population. Statistics of the Indonesia Stock Exchange (IDX) is the source of this data collection., therefore the method used is the Quantitative approach method. The findings of the study show that there is no visible impact of managerial, institutional, or foreign ownership on profit management.